Juvenile Primary Fibromyalgia Syndrome: Advances in Etiopathogenesis, Clinical Assessment and Treatment: A Narrative Review - Claudio Lavarello; Silvana Ancona; Clara Malattia (Biomedicines)
Juvenile Primary Fibromyalgia Syndrome (JPFS) is a complex, multifactorial condition characterized by widespread musculoskeletal pain, often accompanied by sleep disturbances, headaches, cognitive and mood disorders, and fatigue, resulting in a significant impact on the quality of life for affected children, adolescents, and their families. Although recent advances have improved the understanding of the underlying pathophysiological mechanisms and therapeutic approaches, its etiology and optimal treatments remain largely unknown. In this review, we summarize recent advances in the etiopathogenesis, clinical assessment, and treatment of JPFS. Our aim is to support clinicians in the diagnosis and management of JPFS patients, while also highlighting key areas that require further research to improve diagnostic accuracy and therapeutic outcomes.